Fibers, Textiles, and Dress - Droß-Krüpe, Kerstin; Grömer, K. (A Cultural History of Craft in Antiquity)

rota – ratio – res publica. Gesammelte Schriften Helmuth Schneider II

Private Peers’ Disclosure Transparency and Public Firms’ Information Environment - Beyer, Bianca; Flagmeier, Vanessa; Kosi, Urska
This study examines how private peers’ disclosure transparency affects public firms’ information environment, captured through analyst forecast behavior. Focusing on the most important private firms operating in U.S. industries, we investigate whether private peer disclosure—despite differing substantially from public firm disclosure—is incorporated into analysts’ forecasts. In a cross-sectional analysis, we document lower forecast quality in industries where private peers’ disclosure intensity is low. In contrast, when private peers’ disclosure intensity is high, forecast quality does not differ from that in industries with only public peers. We find consistent results for a subsample of U.S. private peers. Consistent with this interpretation, a difference-in-differences analysis documents increased analyst forecast activity around the disclosure dates of private peers. Together, these findings indicate that analysts incorporate private peers’ information when these peers are both economically important and sufficiently transparent, and highlight that variation in private firms’ disclosure intensity generates heterogenous externalities for public firms. Overall, our evidence supports a cost-benefit trade-off in analysts’ information acquisition, and, by documenting the relevance of private peers’ information for public firms, contributes to the debate on the externalities of private firms’ disclosure transparency.

INNOVADE Interdisciplinary Knowledge Base on Digital Democracy - D2.1 - Fuchs, Christian; Friesch, Kevin; Museba, Joel
This report outlines foundations of digital democracy and digital democracy research. It is structured into eight chapters: Chapter 1: Introduction Chapter 2: What is Digital Democracy? Chapter 3: Online Participation Chapter 4: Open Governance Chapter 5: Digital Activism Chapter 6: e-Voting Chapter 7: Global Trends that Influence Digital Democracy Chapter 8: Foreign Interferences in Democracy

Dissemination of information by small caps - Böing, Dennis; Kosi, Urska

Kulturerbe in der Kulturellen Bildung – Potenziale außerschulischen Lernens an der Schnittstelle zwischen ästhetischer Erfahrung und politischer Bildung. - Eikermann, Larissa (KULTURELLE BILDUNG ONLINE)
Keywords: Kulturelle Bildung; Kulturerbe; Kulturelles Erbe; Kunstunterricht; Denkmalpädagogik; Denkmalvermittlung

Deutsch als Zweitsprache, Sprachbildung und Mehrsprachigkeit: Curriculare Grundlagen für die Professionalisierung von Lehrkräften

“They Really Need to Handle, Inspect, and Experience Things” - Schröer, Franz; Tenberge, Claudia (Linköping Electronic Conference Proceedings)
Taking pupils’ diverse needs into account is considered a central requirement of inclusive education (Booth & Ainscow, 2016). These needs are—according to Ainscow’s (2007) inclusive turn—not primarily ‘special educational needs’, but diverse needs of all learners. For the rather segregated German educational system, this endeavour applies especially to primary education, where needs are still developing and pupils are not yet assigned to different types of schooling according to their needs and abilities. Despite a substantial amount of research on pupils’ basic psychological needs for autonomy, competence and social relatedness (Ryan et al., 2022), strategies that technology education teachers apply in this regard are not yet well understood. Besides interventional studies on technology education, indicating effectiveness of self‑directed and action‑oriented teaching and learning, there is a dearth of research on how teachers address different needs as a routine. The purpose of the presented study is therefore to investigate and systematize actions and strategies teachers apply, and to specify how pupils' needs are considered when teaching technology education on a given topic. The overall study used a mixed-methods approach to the question how pupils’ needs are characterized by themselves and by their teachers, and how they were taken into account in a lesson adapted and delivered by the teachers. In the sub-study presented here, participating primary school teachers were interviewed about their consideration of pupils’ needs whilst planning and conducting a technology education unit on the functionality of robots. The results gained from qualitative content analysis of the interviews indicate that although the anticipation of different needs is considered challenging, teachers possess a substantiate amount of practices and strategies to take them into account. The paper systematizes the practices teachers described in structured interviews within strategies and discusses the contribution of taking basic needs into account for inclusive technology education.
Keywords: Technology Education; Inclusion; Basic Needs; Robotics; Mixed Methods; Teachers' Abilities

Vancomycin‐Mediated Binding of DNA Origami Nanostructures to Gram‐Positive and Gram‐Negative Bacteria - Coşkuner Leineweber, Özge; Hofmann, Ulrike; Grundmeier, Guido; Zhang, Yixin; Keller, Adrian Clemens (ChemBioChem)
DNA origami nanostructures (DONs) have promising applications in biomedicine and biosensing, which often require their efficient binding to target cells. By immobilizing the glycopeptide antibiotic vancomycin on DONs, DON binding to Gram‐positive and Gram‐negative bacteria can be facilitated. Here, we investigate how this multivalent binding is affected by the number and arrangement of the vancomycin modifications on two‐dimensional DONs. We find that for both Gram‐positive Bacillus subtilis and Gram‐negative Escherichia coli , binding increases with the number of vancomycin modifications per DON. In general, binding to E. coli is stronger than to B. subtilis , which may be attributed to differences in the architectures of the cell envelopes. Interestingly, for both bacteria, the total number of vancomycin modifications appears to be more important than their arrangement, as DONs with 18 vancomycin molecules on one side show similar binding as DONs with 18 vancomycin molecules distributed over both sides. This enables the attachment of multiple probe molecules to the vancomycin‐free side of the DONs for enhancing detection efficiency without compromising binding affinity. These results may thus provide guidelines for the design and synthesis of vancomycin‐modified DONs for antimicrobial drug delivery and pathogen detection.

Rezension zu: Bieker, Markus: Historische Perspektivität als kommunikatives Konstrukt. Ein Beitrag zur geschichtsdidaktischen Theoriebildung und empirisch-qualitativen Prozessforschung - Grauthoff, Fabian (H-Soz-Kult)

Demonstration of a quantum C-NOT gate in a time-multiplexed fully reconfigurable photonic processor - Pegoraro, Federico; Held, Philip; Lammers, Jonas; Brecht, Benjamin; Silberhorn, Christine (Nature Communications)
The two-qubit controlled-not (C-NOT) gate is an essential component for gate-based quantum circuits. In fact, its operation, combined with single qubit rotations allows to realise any quantum circuit. Several strategies have been adopted in order to build quantum gates. Among them, photonics offers the dual advantage of excellent isolation from the environment and ease of manipulation at the single qubit level. Here we adopt a scalable time-multiplexed approach in order to build a fully reconfigurable architecture capable of implementing a post-selected C-NOT gate with a fidelity of (93.8 ± 1.4)%. We then show how our time-multiplexed platform can be employed to combine a C-NOT and a single qubit gate in order to generate the four Bell states.
Keywords: Photonic Quantum Computing; Time-multiplexing; Quantum Information

Benchmarking that Matters: Rethinking Benchmarking in Continuous Optimisation for Practical Impact - Kononova, Anna V.; van Stein, Niki; Mersmann, Olaf; Bäck, Thomas; Bartz-Beielstein, Thomas; Glasmachers, Tobias; Hellwig, Michael; Krey, Sebastian; Kudela, Jakub; Naujoks, Boris; Papenmeier, Leonard; Raponi, Elena; et al. (Applications of Evolutionary Computation - 29th European Conference, EvoApplications 2026, Held as Part of EvoStar 2026, Toulouse, France, April 8-10, 2026, Proceedings, Part II)

LLM Driven Design of Continuous Optimization Problems with Controllable High-Level Properties - Skvorc, Urban; van Stein, Niki; Seiler, Moritz; Grimme, Britta; Bäck, Thomas; Trautmann, Heike (Applications of Evolutionary Computation - 29th European Conference, EvoApplications 2026, Held as Part of EvoStar 2026, Toulouse, France, April 8-10, 2026, Proceedings, Part II)

Investigating the representation of backchannels and fillers in fine-tuned language models - Wang, Yu; Lao, Leyi; Huang, Langchu; Skantze, Gabriel; Xu, Yang; Buschmeier, Hendrik (Proceedings of the 64th Annual Meeting of the Association for Computational Linguistics)
Backchannels and fillers are important linguistic expressions in dialogue, but often treated as "noise" to be bypassed in modern transformer-based language models. Our work studies the representation of them in language models using three fine-tuning strategies. The models are trained on three dialogue corpora in English and Japanese, where backchannels and fillers are preserved and annotated, to investigate how fine-tuning can help LMs learn their representations. We first apply clustering analysis to the learnt representation of backchannels and fillers, and have found increased silhouette scores in representations from fine-tuned models, which suggests that fine-tuning enables LMs to distinguish the nuanced semantic variation in different backchannel and filler use. We also use natural language generation (NLG) metrics and qualitative analysis to confirm that the utterances generated by fine-tuned language models resemble human-produced utterances more closely. Our findings suggest the potentials of transforming general LMs into conversational LMs that are more capable of producing human-like languages adequately.

Die 'gute' Mutter - Eine diskursanalytische Untersuchung von Mutterschaft in Sozialen Medien - Menzel, Tessa-Marie
In diesem Open-Access-Buch untersucht Tessa-Marie Menzel das Ideal und die diskursive Hervorbringung der 'guten' Mutter in Sozialen Medien. Im Zentrum steht die App Instagram als digitale Öffentlichkeit, in der sogenannte Momfluencerinnen Mutterschaft öffentlich inszenieren und normativ rahmen. Vor dem Hintergrund widersprüchlicher gesellschaftlicher Erwartungen zwischen intensiver Fürsorge und weiblicher Selbstverwirklichung wird mit Hilfe einer Diskursanalyse untersucht, welches Bild der 'guten' Mutter (re-)produziert und legitimiert wird. Anhand von sechs normativen Figuren ‚guter‘ Mutterschaft zeigen die Ergebnisse, dass konkurrierende Anforderungen zu einem scheinbar mühelosen Ideal verschmelzen, bei dem Stress zum Statussymbol wird und Mutterschaft an soziale und ökonomische Privilegien gebunden ist.
Keywords: Mutterschaft; Instagram; Diskursanalyse; Sozialpädagogik; Erziehungswissenschaft

How hard is it to verify a classical shadow? - Karaiskos, Georgios; Rudolph, Dorian; Meyer, Johannes Jakob; Eisert, Jens; Gharibian, Sevag (International Colloquium on Automata, Languages, and Programming (ICALP))
Classical shadows are succinct classical representations of quantum states which allow one to encode a set of properties P of a quantum state rho, while only requiring measurements on logarithmically many copies of rho in the size of P. In this work, we initiate the study of verification of classical shadows, denoted classical shadow validity (CSV), from the perspective of computational complexity, which asks: Given a classical shadow S, how hard is it to verify that S predicts the measurement statistics of a quantum state? We show that even for the elegantly simple classical shadow protocol of [Huang, Kueng, Preskill, Nature Physics 2020] utilizing local Clifford measurements, CSV is QMA-complete. This hardness continues to hold for the high-dimensional extension of said protocol due to [Mao, Yi, and Zhu, PRL 2025]. Among other results, we also show that CSV for exponentially many observables is complete for a quantum generalization of the second level of the polynomial hierarchy, yielding the first natural complete problem for such a class.

Boundary values of diffeomorphisms of simple polytopes, and controllability - Glöckner, Helge; Grong, Erlend; Schmeding, Alexander (Differential Geometry and its Applications)

“It’s the 21st century, but this is still a boy’s club” - Gender, money and power in Inventing Anna - Intveen, Julie (MEIN FACH Englisch Sek II)

Emotionale Aktivierung - Großkrüger, Denise; Roberts, Claire; Schmidt, Rebekka (KUNST+UNTERRICHT (Beilage: IM FOKUS))

Sozial-konstruktivistische Aktivierung - Großkrüger, Denise (KUNST+UNTERRICHT (Beilage: IM FOKUS))